Potential effects of lactoferrin as antiviral and neoadjuvant therapy in pediatric patients with viral gastroenteritis - Alver Prasetya; Robby Soetedjo; Gabriel Tandecxi; Brigitte Leonie Rosadi; Edward Davis; Maureen Miracle Stella; Ignatius Ivan; Linawati Hananta (Hygeia Press di Corridori Marinella, 2021)
Viral gastroenteritis is a prevalent disease in children. Each year, around 111 million children suffer from viral gastroenteritis. Clinical features such as fever, nausea, vomiting, and diarrhea may result in severe cases requiring hospitalization. Current therapies of this disease are symptomatic therapies, which are focused on patient rehydration. Previous studies found that lactoferrin (LF) is a milk protein known to have antiviral potential, suggesting the possibility of utilizing it as an alternative therapy for viral gastroenteritis. This literature review aims to determine the potential effects of LF in treatment and prevention, thereby reducing the incidence and severity of viral gastroenteritis. A literature search for related articles published in the past 20 years was performed on PubMed, EBSCOhost, ProQuest and another source using the main keywords "lactoferrin, viral, and gastroenteritis". There were 6 articles assessed in this review. Several clinical trials have shown that giving LF supplements could significantly reduce the duration and the severity of gastroenteritis, especially with high doses of LF (0.49-1 g). Therefore, the efficacy of LF in pediatric gastroenteritis worked in a dose-dependent manner. However, mixed results were reported in the clinical trials assessing the efficacy of LF against viral gastroenteritis, but this could be due to the low doses of LF used. In conclusion, LF could be used as a complementary treatment against pediatric gastroenteritis, but further studies using high LF doses against pediatric viral gastroenteritis need to be evaluated further.